Meso-scale analysis of angle-ply laminates - Ellyin, Fernand; Zhang, Yunfa; Xia, Zihui (Procedia engineering, 2011)
In this paper, a meso-scale repeated unit cell model for a general [θ]n angle-ply laminate is developed and the implementation of periodic boundary conditions in a finite element analysis for this 3-D model is presented. A nonlinear viscoelastic constitutive model and a post-damage constitutive model based on the concept of a smeared crack are also incorporated in the finite element analysis. The stress-strain response and the damage initiation and propagation for different values of θ are predicted.